Is the vesicular nucleotide transporter a molecular target of eicosapentaenoic acid? - Moriyama, Yoshinori; Hasuzawa, Nao; Nomura, Masatoshi (Frontiers in Pharmacology, 2022)
Vesicular nucleotide transporter (VNUT), an active transporter for nucleotides in secretory vesicles, is responsible for the vesicular storage of ATP and plays an essential role in purinergic chemical transmission. Inhibition of VNUT decreases the concentration of ATP in the luminal space of secretory vesicles, followed by decreased vesicular ATP release, resulting in the blockade of purinergic chemical transmission. Very recently, Miyaji and colleagues reported that eicosapentaenoic acid (EPA) is a potent VNUT inhibitor and effective in treating neuropathic and inflammatory pain and insulin resistance through inhibition of vesicular storage and release of ATP (Kato et al., (2022) PNAS 119: e2122158119). However, our validation study indicated that, in bovine adrenal chromaffin granule membrane vesicles, EPA inhibited the formation of an electrochemical gradient of protons across the membrane with the concentration of 50 % inhibition (IC50) being 1.0 M without affecting concanamycin B-sensitive ATPase activity. Essentially, similar results were obtained with proteoliposomes containing purified vacuolar H+-ATPase. Consistent with these observations, EPA inhibited the ATP-dependent uptakes of ATP and dopamine by chromaffin granule membrane vesicles, with ID50 being 1.2 and 1.0 M, respectively. Furthermore, EPA inhibited ATP-dependent uptake of L-glutamate by mouse brain synaptic vesicles with ID50 being 0.35 M. These results indicate that EPA at sub-M acts as a proton conductor and increases proton permeability across the membrane, regardless of the presence or absence of VNUT, thereby inhibiting non-specifically the vesicular storage of neurotransmitters. Thus, EPA may affect a broader range of chemical transmission than proposed.